THE USE OF READ, COVER, REMEMBER, RETELL (RCRR) IN IMPROVING STUDENTS’ READING COMPREHENSION AT SMA NEGERI 1 TONDANO - Marcella Damima; Paula Hampp; Sanerita T. Olii (Program Studi Pendidikan Bahasa Inggris, 2023)
This research focus on the use of Read, Cover, Remember, Retell (RCRR) in improving students' reading comprehension at SMA Negeri 1 Tondano. The research sample consisted of 31 students at class XI IPA 6. A quantitative research method was used, employing a Pre-Experimental Design form of one group pre-test and post-test design. The instrument used in this research was a multiple-choice test consisting of 25 items. Data were analyzed using mean score formula to see significant differences between the pre-test and post-test scores. The results showed that there was a significant difference between pretest and posttest scores. The result of students’ pre-test was 41,48 and the post-test was 71,61. The different score between pre-test and post-test was 30,13. The result of this research is indicate that mean score of post-test was higher 30,13% more than pre-test. This shows that the use of the RCRR method is effective in improving students' reading comprehension at SMA Negeri 1 Tondano. In addition, students report that the RCRR helps them to focus more and understand the text better. In conclusion, this research recommends that the RCRR method be used as an alternative learning in teaching reading especially reading comprehension in schools.